Tax Avoidance in Mining Sector (Coal Production) Companies Listed on the Indonesia Stock Exchange (2019-2023): The Effect of Transfer Pricing and Profitability - Laksono, Radi; Purnamasari, Dyah (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2025)
This research aims to analyze the influence of transfer pricing and profitability on tax avoidance in coal mining (production) companies listed on the Indonesia Stock Exchange (IDX) for the period 2019-2023. The research method employed is associative with a quantitative approach. The data utilized is secondary data in the form of annual financial reports for the 2019-2023 period from 10 coal mining (production) companies. The study's findings reveal that transfer pricing has a effect leading to increased tax avoidance (evidenced by a lower Cash Effective Tax Rate), and similarly, higher profitability also significantly correlates with increased tax avoidance (lower CETR). This study recommends that companies exercise greater prudence in their transfer pricing strategies and tax compliance in line with high profitability. Furthermore, it advises tax authorities to enhance their supervision of transfer pricing practices and consider profitability in mapping tax compliance risks.